Comparison the use of pure jelly lubricant with xilocain gel in the installation of urine chateters for the patient’s level - Oyoh; Asep Badrujamaludin; Yully Yanny; Tria Firza Kumala (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Aims : This research aims to compare the use of pure jelly with xilocain gel in the installation of urine catheter for the patient’s pain level. Design : The research design used was a quasy experiment using a post test only control group design technique. Methods : This method compared two intervention groups without a pretest. Sample collection using purposive sampling technique. A sample of 60 respondent. The instrument used is numeric ratting scale. Data analysis using Mann Withney test. Results : The results of the research pure jelly mean rank is 44.18 and xilocain gel mean rank is 16.82, with result p-value 0.001 this shows there is a difference in thelevel of pain of patients on the use of pure jelly with xilocain gel in the installation of urinary catheter in General Hospital Soreang Conclusions : It is expected that the result of this study can be considered as one form of development of science based on the evidance of based practice in the management of catheter insertion than the use of xilocain gel can be input into the SPO ( Standard Operating Procedure) in order to reduce pain in patients who have urine catheter, and can be inserted in the one pain management carried out by nurses.